Translation Quality Assessment – from Ontology to Axiology - Kubaszczyk, Joanna (Glottodidactica, 2017)
The subject of the paper is intersubjectivity and verifiability of judgments about the quality of translation. Criteria for identification of a text to be a translation and possibilities of assessing the value of translation based on the classic triad of truth, goodness and beauty are discussed. The starting point for the axiological assessment is the ontic structure of the original. It is shown how a type of relationship between the original and the translation impacts on the assessment of translation.